Analysis of the Implementation of Risk Management to Minimize the Risk of Bad Credit at the Nias Rural Development Savings and Loans Cooperative (KSP3) Gunungsitoli Branch - Seniati Daeli; Aferiaman Telaumbanua; Idarni Harefa; Eduar Baene (Golden Ratio of Data in Summary, 2024)
This study aims to determine the application of risk management carried out by the Nias Rural Development Savings and Loan Cooperative (KSP3) Gunungsitoli Branch in minimizing the risk of bad loans. In this study, the type of research used is a descriptive type with a qualitative approach. Data collection techniques are used through observation, interviews and documentation. To obtain information, the researcher conducted direct interviews with 6 informants, namely branch heads, 2 employees and 3 members of the Nias Rural Development Savings and Loan Cooperative (KSP3) Gunungsitoli Branch. The data analysis techniques used in qualitative research include transcripts of interview results, data reduction, data presentation and conclusion drawn. The results of the study show that the implementation of risk management carried out by the Nias Rural Development Savings and Loan Cooperative (KSP3) Gunungsitoli Branch is carried out through a series of stages, namely risk identification, risk measurement, risk monitoring and risk control. The implementation of risk management to minimize the risk of bad loans has been effectively implemented by KSP3 Nias Gunungsitoli Branch as evidenced by the NPL (Non-Performing Loan) rate from 2020-2022 which is still below 5%.